PENYELESAIAN PROYEK PERUMAHAN DENGAN MENGGUNAKAN METODE PERT (PROGRAM EVALUATION AND REVIEW TECHNIQUE) - Sumbaryadi, Achmad (LPPM Universitas Nusa Mandiri, 2013)
The project is an activity using our resources. A successful project needs to have a good plan, including for the schedule, budget, and raw material used by this project. Project management needs to establish by a project manager who responded with the project. A project meager has to manage the project with a great calculation. The research tried to find out, the application of the PERT method at the company. The result of the research is the company need to establish another way or strategy to create a plan with minimizing cost The company could try the PERT method to raise its efficiency plan.